Clinicopathological analysis of ovarian tumours: a 10 year retrospective study - Naik, Sahana N.; K. S., Sunil Kumar; B., Girija (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Ovarian tumors account for 30% of all cancers of female genital tract which represents the sixth most common cancer and fourth leading cause of death in women. The present study was done with an objective to determine the frequency and distribution of various ovarian tumors and to study their clinical and histopathological presentations. Methods: It is a retrospective observational study of patients with ovarian tumors subjected to surgery in the department of obstetrics and gynecology, SDM College of Medical Sciences and Hospital from January 2005 to December 2015. Results: There were 642 cases comprising of 77.7% of neoplastic lesions and 22.3% of non-neoplastic lesions. Majority of the ovarian tumors (83%) were seen in the age group of 20 to 50 years. Mean age for ovarian tumors was 38 years. Among the neoplastic lesions 84% were benign, 14.2% were malignant and 1.8% were borderline tumors. Surface epithelial tumors were the commonest tumors (60.9%) followed by germ cell tumors (12.8%). Serous cystadenoma was the most common benign tumors (47.1%) followed by mucinous cystadenoma (18.4%). Among the ovarian malignant tumors; serous cystadenocarcinoma was the most common (4.5%) followed by mucinous cystadenocarcinoma (2.6%). Chocolate cysts were the most common among the non-neoplastic lesions (36.4%). Conclusions: Ovarian neoplastic lesions were more common than non-neoplastic lesions. Benign ovarian tumors were common in reproductive age group. The mean age of occurrence for ovarian tumor was 38 years. The most common neoplasm was surface epithelial tumors, of which serous tumors was the commonest. Chocolate cysts were the most frequently encountered histopathological finding among the non-neoplastic lesions.